Clinical, oculographic, and vestibular test characteristics of vestibular migraine. (September 2021) - Young, Allison S; Nham, Benjamin; Bradshaw, Andrew P; Calic, Zeljka; Pogson, Jacob M; D'Souza, Mario; Halmagyi, G Michael; Welgampola, Miriam S
Background: We characterise the history, vestibular tests, ictal and interictal nystagmus in vestibular migraine. Method: We present our observations on 101 adult-patients presenting to an outpatient facility with recurrent spontaneous and/or positional vertigo whose final diagnosis was vestibular migraine (n = 27) or probable vestibular migraine (n = 74). Ictal and interictal video-oculography, caloric and video head impulse tests, vestibular-evoked myogenic potentials and audiometry were performed. Results: Common presenting symptoms were headache (81.2%), spinning vertigo (72.3%), Mal de Débarquement (58.4%), and motion sensitivity (30.7%). With fixation denied, ictal and interictal spontaneous nystagmus was observed in 71.3 and 14.9%, and purely positional nystagmus in 25.8 and 55.4%. Spontaneous ictal nystagmus was horizontal in 49.5%, and vertical in 21.8%. Ictal spontaneous and positional nystagmus velocities were 5.3 ± 9.0°/s (range 0.0–57.4), and 10.4 ± 5.8°/s (0.0–99.9). Interictal spontaneous and positional nystagmus velocities were <3°/s in 91.8 and 23.3%. Nystagmus velocities were significantly higher when ictal ( p < 0.001/confidence interval: 2.908‒6.733, p < 0.001/confidence interval: 5.308‒10.085). Normal lateral video head impulse test gains were found in 97.8% (mean gain 0.95 ± 0.12) and symmetric caloric results in 84.2% (mean canal paresis 7.0 ± 23.3%). Air- and bone-conducted cervical-vestibular-evoked myogenic potential amplitudes were symmetric in 88.4 and 93.4% (mean corrected amplitude 1.6 ± 0.7, 1.6 ± 0.8) with mean asymmetry ratios of 13.0 and 9.0%. Air- and bone-conducted ocular-vestibular-evoked myogenic potentials were symmetric in 67.7 and 97.2% (mean amplitude 9.2 ± 6.4 and 20.3 ± 12.8 µV) with mean asymmetry ratios of 15.7 and 9.9%. Audiometry was age consistent and symmetric in 85.5%. Conclusion: Vestibular migraine is characterised by low velocity ictal spontaneous nystagmus, which can be horizontal, vertical, or torsional, and normal audiovestibular test results.